PELATIHAN STRATEGI PEMASARAN HIJAU UKM KERAJINAN DI KOTA SERANG - Hidayah, Nur; Jessalonica, Chennan (Transpublika Publisher, 2024)
Marketing activities are crucial for keeping products or services relevant in the community. Therefore, implementing sustainable marketing practices is essential to support the long-term viability of the business. The purpose of the PKM activities is to provide insights into how SMEs can manage their marketing efforts to align with environmental and sustainability concerns. However, various problems arise, particularly in executing green marketing strategies to ensure business sustainability. This is often due to a lack of knowledge among partners about green marketing. To address this, PKM activities aim to enhance partners' understanding of green marketing. The method offered in this activity is online training and socialization through Zoom meetings. The material to be delivered includes a basic introduction to green marketing, methods, regulations, benefits, and other related topics. This activity aims to resolve issues faced by partner businesses, help partners understand the importance of green marketing knowledge, and ensure business and product sustainability. The final output of this activity includes publications in journals and intellectual property rights (IPR).